THE EFFECT OF SUSTAINABLE CAREER DEVELOPMENT, GREEN TRAINING, AND SUSTAINABLE WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY WITH EMPLOYEE INVOLVEMENT AS A MEDIATING VARIABLE AT THE PALEMBANG CITY PUPR OFFICE (The International Conference on Sustainable Economics Management and Accounting Proceeding, 2025)
This study aims to analyze the influence of Sustainable Career Development, Green Training, and Sustainable Work Environment on employee productivity at the Palembang City Public Works and Spatial Planning Office (PUPR), with employee involvement as a mediating variable. The approach used in this study is quantitative with a causal research design. This study aims to analyze the influence of Sustainable Career Development, Green Training, and Sustainable Work Environment on employee productivity at the Palembang City PUPR Office, with employee involvement as a mediating variable. Data was collected from civil servants (PNS) who have worked at the PUPR Office for the past five years with a population of 183 people. This study used a non-probability sampling method with a simple random sampling technique, resulting in a sample of 125 respondents. The research method used was cross-sectional with data analysis using PLS-SEM to test the relationship between variables. The results of the study show that Sustainable Career Development and Green Training have a positive and significant influence on employee productivity while the Sustainable Work Environment does not have a significant influence on employee productivity. In addition, employee involvement has been proven to strengthen the influence of Sustainable Career Development and Green Training on productivity.